Temperament and character traits in major depressive disorder: a case control study - Barbara Schwair Nogueira; Renerio Fraguas Júnior; Isabela Martins Benseñor; Paulo Andrade Lotufo; Andre Russowsky Brunoni (São Paulo Medical Journal, 2017)
ABSTRACT BACKGROUND: Patients with major depressive disorder (MDD) have distinct personality traits, compared with control subjects, although the role of anxiety and positive and negative affects in this finding is unclear. DESIGN AND SETTING: A case-control study enrolling 103 antidepressant-free depressed patients and 103 age and gender-matched controls was conducted at the University Hospital, University of São Paulo. METHODS: The self-reported scales of the Positive and Negative Affect Schedule (PANAS), State-Trait Anxiety Inventory (STAI) and Cloninger’s Temperament and Character Inventory (TCI) were applied. Temperament and character traits were compared between groups using multivariate and bivariate analyses of variance (MANOVA and ANOVA). The influence of anxiety and affect was further investigated using ANOVA and mediation analyses. RESULTS: Depressed patients presented higher harm avoidance and lower self-directedness scores than controls. After adjustment for anxiety trait, harm avoidance was no longer significantly different between groups. Mediation analysis revealed that the anxiety trait, but not state-anxiety or affect, fully mediated the influence of group (depressed versus control subjects) on harm avoidance. CONCLUSIONS: Our findings confirm that depressed patients present personality traits distinct from those of controls and suggest that MDD is not directly associated with harm avoidance, but that this effect is fully mediated through the anxiety trait.